2021
DOI: 10.1039/d1nr01058a
|View full text |Cite
|
Sign up to set email alerts
|

Depth mapping of metallic nanowire polymer nanocomposites by scanning dielectric microscopy

Abstract: Polymer nanocomposite materials based on metallic nanowires are widely investigated as transparent and flexible electrodes or as stretchable conductors and dielectrics for biosensing. Here we show that Scanning Dielectric Microscopy...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Scanning dielectric microscopy (SDM) measures the out-of-contact local electrostatic forces acting on the tip, when an AC voltage is applied between the conductive tip and a bottom electrode with the sample in between, obtaining the local capacitance gradient and the relative phase of the tip movement with the external excitation (see Methods section for details of implementation). SDM has extensively been used to map the dielectric and conductive properties (at the kHz-MHz frequency range) of various types of materials, , under different environmental conditions. However, the complex quantification procedure, coupled with its lower sensitivity for materials with a high dielectric constant (usually the case for most ferroelectrics and ionic conductors) has meant SDM is underutilized for probing dielectric properties of ferroelectrics . Complementing SDM is scanning microwave microscopy (SMM), which can be utilized to explore dielectric and conductive phenomena on the nanoscale at higher frequencies (GHz) (see Supporting Information S1 for the correlative high-frequency imaging).…”
Section: Resultsmentioning
confidence: 99%
“…Scanning dielectric microscopy (SDM) measures the out-of-contact local electrostatic forces acting on the tip, when an AC voltage is applied between the conductive tip and a bottom electrode with the sample in between, obtaining the local capacitance gradient and the relative phase of the tip movement with the external excitation (see Methods section for details of implementation). SDM has extensively been used to map the dielectric and conductive properties (at the kHz-MHz frequency range) of various types of materials, , under different environmental conditions. However, the complex quantification procedure, coupled with its lower sensitivity for materials with a high dielectric constant (usually the case for most ferroelectrics and ionic conductors) has meant SDM is underutilized for probing dielectric properties of ferroelectrics . Complementing SDM is scanning microwave microscopy (SMM), which can be utilized to explore dielectric and conductive phenomena on the nanoscale at higher frequencies (GHz) (see Supporting Information S1 for the correlative high-frequency imaging).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Balakrishnan et al used scanning dielectric microscopy to map the depth distribution of MNWs within the MNW/polymer‐based nanocomposites, in a non‐destructive way. [ 467 ] This was achieved thanks to a quantitative analysis of subsurface electrostatic force microscopy measurements with finite‐element numerical calculations. [ 467 ] Milano et al also demonstrated that the electrical resistance tomography (ERT) method can be used to follow in situ the evolution of the conductivity of AgNW networks and observe the origin of their degradation.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…[ 467 ] This was achieved thanks to a quantitative analysis of subsurface electrostatic force microscopy measurements with finite‐element numerical calculations. [ 467 ] Milano et al also demonstrated that the electrical resistance tomography (ERT) method can be used to follow in situ the evolution of the conductivity of AgNW networks and observe the origin of their degradation. [ 468 ] Sannicolo et al used IR imagery to detect the activation of the first percolative paths of sparse AgNW networks, [ 27 ] as well as the origin of the degradation of AgNWs submitted to electrical stress.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The potential of SPM mechanical and dielectric characterization to obtain subsurface information has been widely proven [48][49][50][51], and in the case of cells could be specifically relevant to gather knowledge of internal structure such as smaller cell organelles or internal cell biological processes [51]. The force-volumetric approach used in this work could enable obtaining both local mechanical and dielectric information on the cell simultaneously.…”
Section: 1402 8 Of 13mentioning
confidence: 99%